Impact of Implementation of Nutrition Counseling and Intervention on Toddlers With Malnutrition - Jasmani Jasmani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Malnutrition among toddlers remains a critical public health issue in developing countries. This study evaluated the impact of nutritional counseling and interventions on malnourished toddlers in Walenrang Barat Public Health Center, Luwu Regency, South Sulawesi, in 2024. A pre-experimental design with a one-group pre-test and post-test approach was employed, involving 31 participants selected through total sampling. Data were collected using observation sheets and analyzed with the Wilcoxon test and paired t-test. The results revealed significant improvements in toddlers’ weight and height after the intervention, with average weight increasing from 9.1 kg to 9.4 kg and height from 84.3 cm to 85.4 cm. Statistical analysis yielded a p-value of ρ = 0.000 (α = 0.05), indicating the effectiveness of the interventions. Counseling sessions enhanced parental awareness of balanced nutrition, fostering healthier feeding practices and supporting children’s growth and development. Nutritional interventions, including supplementation, directly addressed nutrient deficiencies, leading to noticeable improvements in toddlers’ physical health and activity levels. These findings highlight the importance of integrating counseling and nutritional interventions as a strategy to combat malnutrition. By equipping parents with knowledge and practical skills, these measures contribute to sustainable improvements in children’s nutritional status and overall health.